2017
DOI: 10.1177/0363546517705635
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play After Shoulder Instability Surgery in National Collegiate Athletic Association Division I Intercollegiate Football Athletes

Abstract: The majority of surgical interventions were isolated arthroscopic stabilization procedures, with no statistically significant difference in RTP rates when concomitant arthroscopic procedures or open stabilization procedures were performed. Athletes who returned to play often played in a higher percentage of games after surgery than before the injury, and many played at the same or a higher level after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…This finding is consistent with previous studies that showed that most glenohumeral subluxations and dislocations were anterior in nature. 8,10,11 In addition, approximately 81% of injuries were caused by contact with another player. This rate is higher than the rates of injuries caused by player contact of 65% to 68% previously reported in all collegiate athletes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding is consistent with previous studies that showed that most glenohumeral subluxations and dislocations were anterior in nature. 8,10,11 In addition, approximately 81% of injuries were caused by contact with another player. This rate is higher than the rates of injuries caused by player contact of 65% to 68% previously reported in all collegiate athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Of the injuries with unknown TL, 57 (53.8%) resulted in the player missing the rest of the season; however, it was impossible to determine how much time remained in the season at the time of injury. Among shoulder instability injuries with known TL, players missed a mean of 8…”
Section: Tl and Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the type of sport could conceivably influence return rates, multiple studies 13,27,29,37,40 have reported rates of 66%-100% for return to the same preinjury level of competition after arthroscopic Bankart anterior shoulder procedures. In a multicenter case series by Robins et al 37 of National Collegiate Athletic Association (NCAA) Division I American football players, an 82% return rate to the same level of play was found after arthroscopic Bankart repair. Similarly, Mazzocca et al 27 reported on a cohort of contact athletes, with 100% of the participants able to return to the same level of play at an average of 5.7 months after undergoing an arthroscopic Bankart repair.…”
Section: Discussionmentioning
confidence: 99%
“…To date, most of the studies regarding outcomes of nonoperative versus surgical management of shoulder instability in professional athletes have been performed on collision athletes, and their findings have mirrored those in the present study regarding a noncollision sport, suggesting superior outcomes in those managed surgically. 9,19,21 Competitive athletes in other sports have also had successful outcomes and return to play after surgical intervention. Mazzocca et al 15 found a 100% rate of return to play in collision and contact athletes after arthroscopic stabilization.…”
Section: Discussionmentioning
confidence: 99%